2018
DOI: 10.2139/ssrn.3140099
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Informal Financial Inclusion in the People's Republic of China

Abstract: Using the 2011 China Household Finance Survey (CHFS) database, we explore the heterogeneous impacts of social networks on informal financial inclusion for urban and rural households in the PRC. We find that social networks significantly increase the probability of households' participation in the informal financial market, augment the size of informal financial transactions, and raise the ratio of informal lending to total household assets. We also identify the mechanisms through which social networks affect h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 89 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Zhu et al (2018) asserted that it is a good way to evaluate the sustainability by measuring the balance of financial inclusion [4]. Social networks can help informal financial inclusion fully and partially guard against systematic risks from the institutional environment (Chai et al, 2018) [31]. It can be learned that strengthening the effects of social networks may help to promote financial inclusion sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhu et al (2018) asserted that it is a good way to evaluate the sustainability by measuring the balance of financial inclusion [4]. Social networks can help informal financial inclusion fully and partially guard against systematic risks from the institutional environment (Chai et al, 2018) [31]. It can be learned that strengthening the effects of social networks may help to promote financial inclusion sustainability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kabakova and Plaksenkov (2018) showed that three configurations of factors affect financial inclusion: social, technological and economic factors. Chai et al (2018) found that social networks significantly increase the probability of households’ participation in the informal financial market, amplify the size of informal financial transactions and raise the ratio of informal lending to total household assets.…”
Section: Theory and Review Of Literaturementioning
confidence: 99%